Interrater reliability of the new sport-specific evidence-based classification system for para Va'a - Rosén, J. S.; Goosey-Tolfrey, V. L; Tolfrey, K.; Arndt, A.; Bjerkefors, A. (Adapted Physical Activity Quarterly, 2023)
The purpose of this study was to examine the interrater reliability of a new evidence-based classification system for Para Va'a. Twelve Para Va'a athletes were classified by three classifier teams each consisting of a medical and a technical classifier. Interrater reliability was assessed by calculating intraclass correlation for the overall class allocation and total scores of trunk, leg, and on-water test batteries and by calculating Fleiss`s kappa and percentage of total agreement in the individual tests of each test battery. All classifier teams agreed with the overall class allocation of all athletes, and all three test batteries exhibited excellent interrater reliability. At a test level, agreement between classifiers was almost perfect in 14 tests, substantial in four tests, moderate in four tests, and fair in one test. The results suggest that a Para Va'a athlete can expect to be allocated to the same class regardless of which classifier team conducts the classification.